2020
DOI: 10.1021/acs.jpca.0c08646
|View full text |Cite
|
Sign up to set email alerts
|

Multireference Description of Nickel–Aryl Homolytic Bond Dissociation Processes in Photoredox Catalysis

Abstract: Multireference electronic structure calculations consistent with known experimental data have elucidated a novel mechanism for photo-triggered Ni(II)-C homolytic bond dissociation in Ni 2,2'bipyridine (bpy) photoredox catalysts. Previously, a thermally assisted dissociation from the lowest energy triplet ligand field excited state was proposed and supported by density functional theory (DFT) calculations that reveal a barrier of ~30 kcal mol-1. In contrast, multireference ab initio calculations suggest this pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 57 publications
6
58
0
Order By: Relevance
“…Irradiation of isolated (dtbbpy)­Ni II ( o -Tol)­(Cl) ( 21 ) in the presence of a radical trap provided no evidence of chlorine radical generation by electron paramagnetic resonance (EPR) spectroscopy, although this does not necessarily reflect a lack of chlorine radical formation . Instead, irradiation of this isolated Ni­(II) aryl chloride complex resulted in exclusive trapping of aryl radicals in low conversion (Ni­(II)–Ar BDFE = 35 kcal/mol) . Therefore, we expect that other pathways, specifically oxidation of Ni by the photocatalyst, could be outcompeting this step under catalytically relevant conditions.…”
Section: Mechanistic Investigationsmentioning
confidence: 99%
“…Irradiation of isolated (dtbbpy)­Ni II ( o -Tol)­(Cl) ( 21 ) in the presence of a radical trap provided no evidence of chlorine radical generation by electron paramagnetic resonance (EPR) spectroscopy, although this does not necessarily reflect a lack of chlorine radical formation . Instead, irradiation of this isolated Ni­(II) aryl chloride complex resulted in exclusive trapping of aryl radicals in low conversion (Ni­(II)–Ar BDFE = 35 kcal/mol) . Therefore, we expect that other pathways, specifically oxidation of Ni by the photocatalyst, could be outcompeting this step under catalytically relevant conditions.…”
Section: Mechanistic Investigationsmentioning
confidence: 99%
“…This would be particularly valuable as routine density functional theory calculations fail to accurately compute electronic structures and energies of Ni-bipyridine systems. 27,28 To this end, we report the synthesis of the well-defined complex [( CO 2 Et bpy)NiCl]4 (1) and present our findings regarding its speciation and oxidative addition with aryl halides ( CO 2 Et bpy = diethyl 2,2′-bipyridine-4,4′-dicarboxylate).…”
Section: Introductionmentioning
confidence: 99%
“…For photoexcited Ni-mediated C–O cross-coupling reactions between aryl halide and carboxylic acid, 7 a several mechanisms have been suggested. 8 The transient absorption spectroscopic (TAS) studies of catalytically-relevant Ni II (2,2′-bipyridine; bpy)(aryl)Cl and Ni II (bpy)(aryl)(acetate) complexes have revealed that Ni-to-bpy charge transfer (CT) transitions lead to a long-lived excited state ( τ = 4 ns). 8 a , c In combination with transient infrared spectroscopy, Doyle et al has defined this state to be a triplet d–d excited state, which is proposed to induce Ni–C bond homolysis in Ni II (bpy)(aryl)Cl on the basis of radical trapping experiment.…”
Section: Introductionmentioning
confidence: 99%